Legal Culture of Illegal Parking Attendants in South Jakarta - Lintang Aminda Kuswara; Fokky Fuad (Universitas Muhammadiyah Tangerang, 2026)
Illegal parking attendants in South Jakarta have developed into a complex legal and social problem. There are two categories of licensed and unlicensed illegal parking attendants. With the increasing number of vehicles in Indonesia, illegal parking attendants take advantage of this situation to earn money illegally, breaking the law and often accompanied by acts of thuggery, which creates fear in the community. The formulation of the problem in this study is how the legal culture surrounding illegal parking attendants in South Jakarta? The research method used is socio-legal by interviewing illegal parking attendants, local landowners, riders at the local location, and the South Jakarta Transportation Department. Then, this data is analyzed to find the factors that encourage the existence of illegal parking attendants and the legal culture that surrounds illegal parking attendants. The results show that many people are forced to become illegal parking attendants due to economic factors and pressure from certain individuals. The result revealed that this condition is exacerbated by the lack of supervision from law enforcement. Controlling illegal parking attendants needs to be done in stages by involving the local community to create a safer and more orderly environment.Keywords :Â Economic Factors, Illegal Parking Attendants, Law Enforcement, Legal Culture.Â